"And Reuben Went" (Gen 30, 14-18; 35, 22a) – For his Mother's Sake or for his Own?. Issue 2 (2nd July 2020) - Jacobsen, Lea
ABSTRACT: In ancient households, it was not always the son who was born first who was granted the birthright. There were certain circumstances in which the father would prefer his younger son over him. But did the first-born son, when realizing that his status was threatened, submissively accept his fathers' intentions to deprive him of his status? This question is examined in the light of the stories about Reuben (Gen 30, 14-18; 35, 22a). Jacob's inclination to prefer the son of Rachel prompted Reuben to act in order to secure his status as the first-born. His awareness of the crucial power of influence of a dominant mother made him act in order to strengthen the position of his mother, Leah, and in this way to make her able to influence Jacob to grant him the birthright.